Association between triglyceride-glucose index and papillary thyroid carcinoma among Chinese adults with thyroid nodules - Song, Chunyan; Ping, Miaomiao; Lin, Ling; Meng, Xing; Lan, Yun; Tong, HuaCheng (Frontiers in Endocrinology, 2025)
BackgroundGrowing evidence has demonstrated that the Triglyceride-Glucose (TyG) index, a reliable and widely recognized marker of insulin resistance, is strongly associated with the development various of types of cancer. For instance, previous studies have demonstrated that elevated TyG index levels are significantly associated to an increased risk of different cancers. Insulin resistance, as reflected by the TyG index, may contribute to tumorigenesis through multiple pathways, including promoting cell proliferation, angiogenesis, and inhibiting apoptosis. Despite these findings, research on the association between the TyG index and papillary thyroid carcinoma(PTC) in Chinese populations is scarce. Given the rising thyroid malignancy incidence, clarifying this relationship is crucial for clinical and public health.ObjectiveTo explore the association between the TyG index and papillary thyroid carcinoma prevalence.MethodsThis cross-sectional study included patients who underwent fine-needle aspiration of thyroid nodules at Nanjing Tongren Hospital from June 2018 to December 2024. A multivariate logistic regression model was used to examine the association between the TyG index and papillary thyroid carcinoma. Furthermore, stratification and interaction analyses were performed to assess the stability of the association across various subgroups. Moreover, sensitivity analysis further confirmed the stability of the findings.ResultsThis study ultimately enrolled 396 patients (mean age 47.8 ± 12.7 years,71.0% females), with the TyG index odds ratio increasing across tertiles. Compared to T1, adjusted ORs for T2 and T3 in papillary thyroid carcinoma were 1.28 and 3.37, respectively. Subgroup and sensitivity analyses supported the results.ConclusionsThis study suggests that TyG index may serve as a valid biomarker for the prediction of papillary thyroid carcinoma in patients with thyroid nodules, although large prospective studies are needed to confirm these findings.